OVULATORY FOLLICULAR DEVELOPMENTS AND PLASMA PROGESTERONE PROFILES IN SUPEROVULATED DAIRY COWS - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRACT: A study concerning follicular development and plasma progesterone concentrations had been conducted in 9 heads of superovulated dairy cows. Superovulatory treatments consisted of treatment I with multiple injection of FSH 6 - 6, 5 - 5. 4 - 4 and 3 - 3 AU with solvent of aquabidest